2016
DOI: 10.1177/2158244016656392
|View full text |Cite
|
Sign up to set email alerts
|

Street Smarts ↔ Book Smarts

Abstract: This article describes the development, implementation, and evaluation of an interdisciplinary undergraduate course embedded within a campus–community partnership initiative involving McMaster University School of Nursing, and three urban priority neighborhoods in Hamilton, Ontario, Canada. Students worked together with community residents and faculty to address selected priority community issues identified by neighborhood members. Using the qualitative interpretive description method, the evaluation explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The costs and benefits can be tangible or intangible (Goemans, 2016). Important tangible benefits noted by many studies were access to the university and its resources, such as student-volunteers (Oberg De La Garza & Moreno Kuri, 2014;Schaffer, Hargate, & Marong, 2015;Valaitis et al, 2016). Similarly, many case studies reported that their CSL/CUP increased the assets of community members or the organization, such as participant health benefits, skill development, organizational capacity, and social integration (Apatu, Slawson, & Gonzalez, 2013;Bucher, 2012;Costandius et al, 2014;Jovanović & Filipović, 2013;Wilson, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The costs and benefits can be tangible or intangible (Goemans, 2016). Important tangible benefits noted by many studies were access to the university and its resources, such as student-volunteers (Oberg De La Garza & Moreno Kuri, 2014;Schaffer, Hargate, & Marong, 2015;Valaitis et al, 2016). Similarly, many case studies reported that their CSL/CUP increased the assets of community members or the organization, such as participant health benefits, skill development, organizational capacity, and social integration (Apatu, Slawson, & Gonzalez, 2013;Bucher, 2012;Costandius et al, 2014;Jovanović & Filipović, 2013;Wilson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…4. Both the community organization partner and the university partner believe the CSL/CUP is beneficial to the community and students (Gazley et al, 2013;Oberg De La Garza & Moreno Kuri, 2014;Valaitis et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…KMR and BA spoke extensively about the benefits and reciprocity that the KW CSL initiative affords their organizations, and the organizations' beneficiaries, including students and Market customers. Mutual benefit, a condition of successful CSL initiatives, as defined by Janke (2013) as "a win-win relationship, [that] suggests equity -that partners achieve the outcomes that are just and meaningful to them" (p. 4) is pervasive in the literature (Andrée et al, 2014;Gazley et al, 2013;Kreulen et al, 2008;Marullo et al, 2009;Oberg De La Garza & Moreno Kuri, 2014;Valaitis et al, 2016). If the CSL initiative is based on a community-university partnership that cultivates mutual benefit, there is more potential for this pedagogical method to foster social transformation (Chupp & Joseph, 2010;Davidson et al, 2010;Maistry, 2014;Rutherford et al, 2011).…”
Section: Reciprocity In the Relationshipmentioning
confidence: 99%
“…KMR does take the time to co-teach a class with BA at the beginning of the semester and is involved with the debriefing at the end of the term, as she feels this is beneficial to her learning and process, and she enjoys this time with the students. Inviting community leaders into the classroom allows for the exchange of ideas, relationship building, and the integration of community members into the university setting, which can enable more equitable relationships among community partners, faculty, and students (Martinez et al, 2012;Valaitis et al, 2016). There is a balance to be struck; faculty cannot expect the community partner to take on the role of educator or mentor unless that is explicitly agreed to as a valueadded component for the community partner organization (Clayton et al,2010;Sandy & Holland, 2006).…”
Section: Scaffolded Experiential Learning Environmentmentioning
confidence: 99%